A rectangular CSRR based microstrip UHF reader patch antenna for RFID applications - Syamimi Mohd Norzeli; Ismarani Ismail; Norashidah Md Din; Mohd Tarmizi Ali; Ali Abd Almisreb; Ammar Ahmed Alkahtani (Institute of Advanced Engineering and Science, 2020)
This paper presents a compact microstrip ultra-high frequency (UHF) reader patch antenna with complementary split ring resonator (CSRR) for radio frequency identification (RFID). The total size of the antenna is 208 × 208 × 1.6 mm3. The proposed antenna is designed, fabricated and measured in order to verify the proposed concept. The characterization for radiation parameters, like return loss, radiation pattern and antenna gain have been done experimentally. The proposed antenna is operated at 921 MHz for and achieved a gain of 8.285 dBi. All simulations in this work have been carried out by means of the commercial computer simulation technology (CST) software. In compare to the simulated results, the measured outcomes are promised.